The Engaged University : Exploring Mutuality and Reciprocity Between and Within Communities Inside and Outside Universities Through ACES - Katherine, Wimpenny; Sylvester, Arnab; Fitri Suraya, Mohamad; Thi Thom Thom, Nguyen; Muhibuddin, Fadhli (Palgrave Macmillan Cham, 2023)
This chapter explores the roles of universities within the context of Community Engaged Scholarship from the perspectives of ACES—A Community-Centered Educational Model for Developing Social Resilience—a collaboration between universities and communities in the UK, Malaysia, Indonesia, and Vietnam. Using a reflective approach to strategize and design activities across the three Southeast Asian countries, it is clear that cross-border analysis assists partners in comprehending and responding to situational challenges in their localities. Universities are fertile grounds to experiment with new ideas, and translating the ideas to communities requires an empathetic focus on academic-community engagement and co-creation. This chapter elaborates on the processes of onboarding and training educators and community players in an evidence-driven playful, frugal approach to bridging formal and informal educational contexts and spaces. We discuss the mindsets and values for mutually beneficial partnerships between academics and the community in considering ways to address societal challenges.